KAJIAN PERUBAHAN AROMA DAN KADAR AIR BLENDING KOPI ARABIKA (Coffea arabica L) DAN ROBUSTA (Coffea canephora L) SELAMA PENYIMPANAN DENGAN VARIASI KEMASAN MENGGUNAKAN SISTEM PENGENALAN POLA - , SURYA ABDUL MUTTALIB, Dr. Joko Nugroho Wahyu Kartiko, S.TP, M.Engg ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In Indonesia, there are two types of coffee grown i.e Robusta and Arabica. Arabica coffee has higher quality flavor than Robusta, but it has less production. If both types are combined, there fore probably produce a good flavor quality with high taste and intense color. The distinctive aroma come from roasting process, which lead to physical and chemical changes in the coffee beans. Usually, organoleptic evaluation of coffee roasted is traditionally done on human senses. After roasted, the aroma quality of coffee grown is decreased quickly, so it is necessary to have good storage conditions and proper packaging. Evaluating the aroma quality of coffee grown use Electronic Nose that has four sensor i.e TGS 822, TGS 825, TGS 826 and TGS 2602. Today, Artificial Neural Network (ANN) is an attractive tool for modeling complex processes. This study aims to classify Arabica and Robusta coffee blends that were roasted and then stored in different packaging variations based on the results of the quantitative value Electronic Nose using pattern recognition ANN and PCA. This research used 3 treatment i.e blending, package and temperature storage. The percentage Arabica : Robusta blends coffee were used respectively: 100:0%, 75:25%, 50:50%, 25:75, 0:100%. 3 types of packages were used i.e : aluminum foil, paper and glass. 2 temperature storages are cool temperatures (15 Â°C) and absolute temperatures (27Â°C). ANN used bacpropagation method, the MSE 1 x 10 -1 , maximum epoch 300000, 4 pieces hide layer. 70% of the data were used for training and 30% for testing. The maximum blends Arabica and Robusta is 75 % : 25% with grade 1. Aluminum foil packaging are better in protecting the coffee powder during storage compared to paper and glass packaging. Grown coffee is better stored in cool temperatures compared to absolute temperature. ANN is able cluster blends coffee Arabica and Robusta coffee with R value = 0.97 and the accuracy value 75% for recognizing the type of coffee blending and 70.6% for recognizing of coffee during storage. PCA can reduce the data so there is no redundancy in the Arabica and Robusta coffee blending with the aroma sensor input value.